COMPARATIVE IMMUNOHISTOCHEMICAL EVALUATION OF E-CADHERIN AND Β-KATENIN EXPRESSION IN METASTATIC AND NON-METASTATIC BREAST CANCER OF NON-SPECIFIC TYPE - M. V. Mnikhovich; L. V. Kakturskiy; T. V. Bezuglova; K. Yu. Midiber; K. V. Bun'kov; A. G. Erzieva (ABV-press, 2018)
Objective: an immunohistochemical analysis of the features of expression, distribution and interaction of E-сadherin and β-сatenin proteins in primary mammary tumors. Materials and methods. The study group consisted of 148 relevant patients with breast cancer (BC), including patients with metastases in lymph nodes (n = 12) and liver (n = 45). E-сadherin and β-сatenin expression on BC cells was determined using immunohistochemical method with specific antibodies. Results. It was shown that the reduction and the total absence of E-сadherin expression was observed much more often in patients with BC with metastases in liver, than in patients without metastases (70 % of cases versus 30 % of cases respectively). An increase of cytoplasmic immune reactivity and a nuclear translocation of β-сatenin are found in more than 80 % cases of BC with metastases.Conclusion. The changes in the expression of E-сadherin and β-сatenin in tumor cell can be considered as factors of a non-favorable prognosis of BC. The emergence of β-сatenin expression indicates the activation of a signaling pathway which is triggered by the aberrant expression of epithelial cadherins leading to an increased mobility and invasion of tumor cells.